The investigation of physiological data using the theory of complex systems - Bikulčienė, Liepa; Poderienė, Kristina; Butkevičiūtė, Eglė; Landauskas, Mantas (Lietuvos matematikos rinkinys, 2015)
This paper presents a complex dynamic system assessment method based on Hankel matrix rank and inter-relationships between elements of the system evalution method. The possibilities of methods application for various physiological data measure and evaluation are introduced. The international project CareWare for portable sensors and systems development is briefly presented.
Keywords: complex systems; ECG; matrix analysis; wearable sensors